Lithium–Oxygen Batteries: Sustainable Redox Mediation for Lithium–Oxygen Batteries by a Composite Protective Layer on the Lithium‐Metal Anode (Adv. Mater. 5/2016). Issue 5 (February 2016) - Lee, Dong Jin; Lee, Hongkyung; Kim, Yun‐Jung; Park, Jung‐Ki; Kim, Hee‐Tak
Abstract : As described on page 857, synergic combination of a soluble redox mediator and a protected lithium (Li) metal electrode is successfully demonstrated by J.‐K‐ Park, H.‐T. Kim, and co‐workers by exploiting a redox mediator of 2, 2, 6, 6‐tetramethylpiperidinyl 1‐oxyl (TEMPO) and a composite protective layer (CPL). Self‐discharge, resulting from extensive migration and chemical reduction of the oxidized TEMPO can be suppressed by a simple coating of a CPL on the Li metal surface. Building a selective barrier to redox mediators provides an impetus for sustainable redox mediation, resulting in robust cycling of lithium–oxygen batteries.